Investigating the Spatial Pattern of Older Drivers’ Eye Fixation Behaviour and Associations with Their Visual Capacity (Journal of Eye Movement Research, 2016)
Visual capacity generally declines as people age, yet its impact on visual search patterns along different road sections of actual driving still remains undocumented. In this on-road driving study, we simultaneously recorded 30 older drivers’ eye movement and precise vehicle movement trajectories. The vehicle positions were linked to every eye fixation of individual drivers so that we know the locations of a driver's gaze origin in geospatial coordinates. Spatial distribution pattern of drivers’ eye fixations (duration and frequency) were then analysed. We further investigated the associations between older drivers’ visual capacity (processing speed, divided and selective attention) and their eye fixation patterns in various driving manoeuvres. The results indicate that driving scenarios have significant impact on older drivers’ visual patterns. Older drivers performed more frequent eye fixations when manoeuvreing through roundabouts, while they tended to fixate on certain objects much longer during straight road driving. The key findings show that the processing speed and divided attention of older drivers were associated with their eye fixations at complex right-turns; drivers with a lower capacity for selective attention performed less frequent eye fixations at roundabout manoeuvres. This study has also demonstrated that visualisation and spatial statistics are effective and intuitive approaches in eye movement analysis.